1999
DOI: 10.1016/s0376-7388(99)00028-9
|View full text |Cite
|
Sign up to set email alerts
|

Static protein adsorption, ultrafiltration behavior and cleanability of hydrophilized polysulfone membranes

Abstract: A systematic study on the in¯uence of incrementally increased hydrophilicity of UF membranes made from chemically modi®ed polysulfone on static protein adsorption, protein ultra®ltration performance and cleanability was performed. Hydrophilicity was imparted to the polymeric backbone either by carboxylation or sulfonation. Membranes with 100% retention towards sulfhydryl modi®ed bovine serum albumin (cys-BSA) were made by the phase inversion process from unmodi®ed polysulfone, ®ve carboxylated polysulfones (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(87 citation statements)
references
References 25 publications
5
81
1
Order By: Relevance
“…Chemical modifications, such as amination [20][21][22], sulfonation [23][24][25], and carboxylation [26][27][28], have been used to impart hydrophilicity to hydrophobic PSF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modifications, such as amination [20][21][22], sulfonation [23][24][25], and carboxylation [26][27][28], have been used to impart hydrophilicity to hydrophobic PSF.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Guiver et al [26] reported the carboxylation of polysulfone (PSF) via a direct lithiation method followed by carbon dioxide and acid treatment. The chemical [26,33,34] and separation properties of these materials as RO and UF membranes [27,28] have been reported in the literature. Here, CPSFs were prepared as new supporting membrane materials for FO membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilic/hydrophobic character of membrane material plays a relatively important role in the interaction between protein and membrane. Since hydrophilic surface preferentially adsorbs water rather than solutes, many researchers have followed the idea of increasing the hydrophilicity of a membrane material with the goal of reducing protein fouling and/or protein adsorption (Mockel et al, 1999). Herein, the surfaces of the PES and some typical modified PES membranes (Copolymer of poly (acrylonitrile-co-acrylic acid), PAN-AA, modified PES membranes with the ratios of the copolymer to PES of 0/16, 0.4/16 and 0.6/16, respectively; and BSA grafted membranes following the copolymer/PES blended membranes) were studied in relation to the adsorption of BSA and FNG in vitro, data are shown in Fig.…”
Section: Protein Adsorptionmentioning
confidence: 99%
“…However, the hydrophobic behaviour prevents its use in several areas such as in water treatment. In order to overcome this drawback, some researchers have proposed the incorporation of hydrophilic groups, to increase the polymer hydrophilicity which improves the membrane water-permeability and reduces membranefouling [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Membranes were prepared by (i) substitution with functionalized groups, (ii) by polymer graft modification or (iii) by surface modification of prefabricated membranes [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%